SCIDOT-39. K16ApoE ENHANCES Aβ-ASSOCIATED 11C-PiB DEPOSITION AND PET SIGNAL IN APP/PS1 TRANSGENIC MICE. (11th November 2019) - Brown, Desmond; Sarkar, Gobinda; Decklever, Teresa; Curran, Geoffry; Sarkar, Ameet; Schmeichel, Ann; Swaminathan, Suresh; Kandimala, Karunya; Jenkins, Robert; Burns, Terry; Lowe, Val
Abstract: OBJECTIVE: The K16ApoE peptide enhances delivery of multiple agents across the blood-brain barrier (BBB). Transgenic mouse models are central to elucidating the underlying pathophysiology of Alzheimer's Disease (AD) and provide a system for evaluating novel therapeutic strategies. PET imaging plays a central clinical role in diagnosing human cases of AD but has had variable performance in mouse models. We investigated the role of K16ApoE to enhance delivery of a radiolabeled PET imaging tracer, 11C-PiB and assess whether this corresponds to improved PET sensitivity in APP/PS1 transgenic mice. METHODS: Brain-delivery of 11C-PiB was accomplished by successive injections of K16ApoE and 11C-PiB. Distribution of 11C-PiB to the brain and heart was quantified via dynamic PET/CT imaging and digital autoradiography. RESULTS: K16ApoE increased the brain uptake of 11C-PiB in both wild-type (WT) and APP/PS1 mice. Administration of K16ApoE increased the PET standard uptake value of 11C-PiB at 5 minutes in WT mice from 1.132 to 2.963 (p=0.006) and in APP/PS1 mice from 0.842 to 3.268 (p=0.016). Enhancement peaked at 5 minutes. Binding was reversible with similarly increased kinetics in both WT and APP/PS1 mice. The absolute values were higher in APP/PS1 mice suggesting increased retention. The increased retention in APP/PS1 mice was consistent with specific binding to A-beta plaques as unlabeled PiB reduced 11C-PiB signal retention. CONCLUSION: K16ApoE mediates enhancement of 11C-PiB signal in APP/PS1 mice brains with increased PET sensitivity. There is increased uptake kinetics in both WT and APP/PS1 mice with specific A-beta plaque binding in the latter. This enhanced delivery of the PET tracer has implications for development and testing of new hypotheses and the efficacy of novel therapeutic paradigms. K16ApoE has potential for improving delivery of several agents across the BBB. This has implication for delivery of diagnostic and therapeutic agents for neurodegenerative and neuro-oncologic diseases.